2022
DOI: 10.3390/molecules27072048
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Type I Receptor (AT1R): The Gate towards COVID-19-Associated Diseases

Abstract: The binding of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike glycoprotein to its cellular receptor, the angiotensin-converting enzyme 2 (ACE2), causes its downregulation, which subsequently leads to the dysregulation of the renin–angiotensin system (RAS) in favor of the ACE–angiotensin II (Ang II)–angiotensin II type I receptor (AT1R) axis. AT1R has a major role in RAS by being involved in several physiological events including blood pressure control and electrolyte balance. Following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 151 publications
(311 reference statements)
0
23
0
Order By: Relevance
“…In addition to vasoconstriction and cytokine production, it causes several harmful effects on the vascular wall. This is largely due to its action on the angiotensin II type 1 (AT1) receptor [ 133 ]. Higher levels of endothelial Ang II trigger the production of reactive oxygen species (ROS) and result in the breakdown of nitric oxide (NO) production by reducing endothelial nitric oxide synthase (eNOS).…”
Section: Covid-19 and Its Effect On The Vasculaturementioning
confidence: 99%
“…In addition to vasoconstriction and cytokine production, it causes several harmful effects on the vascular wall. This is largely due to its action on the angiotensin II type 1 (AT1) receptor [ 133 ]. Higher levels of endothelial Ang II trigger the production of reactive oxygen species (ROS) and result in the breakdown of nitric oxide (NO) production by reducing endothelial nitric oxide synthase (eNOS).…”
Section: Covid-19 and Its Effect On The Vasculaturementioning
confidence: 99%
“…Neutrophil accumulation can lead to alveolar epithelial cell loss through its prooxidative role and the development of acute respiratory distress syndrome (ARDS) [ 67 ]. Therefore, pregnant women required extensive follow up and monitoring since severe infection and pulmonary deterioration lead to preterm birth in many reported cases [ 5 ]. That was the case of a COVID-19-positive pregnant woman, at 34 weeks, who developed severe ARDS after 4 days of fever and dyspnea.…”
Section: The Effect Of Covid-19 In Pregnant Womenmentioning
confidence: 99%
“…The main symptoms of the SARS-CoV-2 infection disease include a dry cough, dyspnea, and fever. Fatigue, musculoskeletal discomfort, headaches, gastrointestinal problems, and a loss of smell and taste are also well-documented [ 4 , 5 , 6 ]. More studies are now investigating the effects of a SARS-CoV-2 infection on systems other than the respiratory system [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study suggested that the SARS-CoV2 spike protein on the viral envelope binds to its receptor, angiotensin-converting enzyme 2 (ACE2), causes downregulation of its activity on the target cell, which is involved in lung physiology and pathology through Renin–Angiotensin (RAS) and Kinin–Kallikrein (KKS) systems [ 6 ]. The downregulation of ACE2 activity decreases its ability to cleave angiotensin I (AngI) and angiotensin II (AngII) to Ang-(1–9) and Ang-(1–7), respectively, leading to an increased level of AngII and hyperactivation of the angiotensin II type 1 (AT1) receptor [ 7 , 8 ]. AngII–AT1R axis that regulates vasoconstrictive, proinflammatory, profibrotic, and prooxidative effects is a potential mechanism of cytokine storm and an acute respiratory distress syndrome (ARDS) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%